Changes in labor relations and work in Colombia: Starting a century with transformations (2007)
This article studies the changes in labor relations and work that occurred at the end of the past and the beginning of the 21st centuries, in Colombian industry. In terms of theory, it draws on the analytical framework proposed by the M.I.T. team based on the 'strategic options of the actors;' methodologically, it approaches the topic through six case studies, using qualitative techniques such as non-participative observation, the semi-structured interview of business actors (directors, workers and labor union representatives) and documentary analysis. On one hand, conclusions validate the pertinence of the analytic framework proposed by M.I.T. in the study of labor relations, in the sense of giving a central role to the company as a unit for analysis and to the strategies of the business actors. Nevertheless, the author calls attention to the need for incorporating the political sphere in this framework, in order to obtain an adequate interpretation of the construction of business mentalities. On the other hand, it verifies the role that total quality strategy has played in transforming labor relations and work in the case studies analyzed.